2009
DOI: 10.1042/cs20080540
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation and disease: protective effects of hyperbilirubinaemia

Abstract: Complement, an important effector mechanism of the immune system, is an enzymatic cascade of approx. 30 serum proteins leading to the amplification of a specific humoral response. It can be activated through the classical or alternative pathways, or through the mannose-binding lectin pathway. The activation of the classical pathway is initiated by the binding of the C1 component to antigen-bound antibodies, known as immunocomplexes. C1 is a complex of one molecule of C1q, two molecules of C1r and two molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 114 publications
0
55
0
1
Order By: Relevance
“…In agreement with previous studies, we also found an inverse correlation of hs-CRP with bilirubin [9,10], which is clearly in line with allegedly anti-inflammatory properties of bilirubin. Bilirubin is known to interfere with expression of adhesion molecules VCAM-1 and ICAM-1 [1], with activity of the complement system [38] and with T cell differentiation [39]. Hence, it is conceivable that anti-inflammatory and anti-oxidative effects of bilirubin may both contribute to less low-grade chronic inflammation in MetS [3,15,18,25,26,40].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous studies, we also found an inverse correlation of hs-CRP with bilirubin [9,10], which is clearly in line with allegedly anti-inflammatory properties of bilirubin. Bilirubin is known to interfere with expression of adhesion molecules VCAM-1 and ICAM-1 [1], with activity of the complement system [38] and with T cell differentiation [39]. Hence, it is conceivable that anti-inflammatory and anti-oxidative effects of bilirubin may both contribute to less low-grade chronic inflammation in MetS [3,15,18,25,26,40].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that unconjugated bilirubin inhibits complement activation via interfering with the interaction between C1 component of complement and immunoglobulins. 19 Moreover, heme oxygenase 1 and heme degradation products could attenuate complement-mediated acute inflammation and protect human vascular endothelial cells against complement-mediated injury. 20 In addition, our previous studies have observed that serum bilirubin has a tight correlation with baPWV.…”
Section: Discussionmentioning
confidence: 99%
“…NO reacts with superoxide to form peroxynitrite (which can induce protein oxidation) and leads to vascular calcification (4). NO bioavailability is gradually reduced (5), leading to vasoconstriction (6) and vascular smooth muscle cell (VSMC) proliferation (7). Biliverdin reductase is expressed on the cell surface of leukocytes and catalyzes the conversion of biliverdin (BV) to bilirubin (UCB).…”
Section: Potential Protective Effects Of Bilirubinmentioning
confidence: 99%